If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7 + 3xN = 5 Solving 7 + 3xN = 5 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -7 + 3xN = 5 + -7 Combine like terms: 7 + -7 = 0 0 + 3xN = 5 + -7 3xN = 5 + -7 Combine like terms: 5 + -7 = -2 3xN = -2 Divide each side by '3N'. x = -0.6666666667N-1 Simplifying x = -0.6666666667N-1
| -4.5x=90 | | x^2+3x+55=180 | | C/10-2=0 | | -27+11x=9x+23 | | -19=3n+13 | | 0.5=-2x+8.1 | | 25m+40=240 | | 77=7(m+4) | | 2f(-4)=5x-5 | | 8x+5-10x=-6-x | | x+10+x+(3x-5)=180 | | 38=3x+y | | (3y-7)+(-4y-8)= | | 40.000+1.000x=60.000 | | 1.12x-2/4 | | 1-7/12-3/4 | | 19/.75 | | 5x-2x+2x=-5-8+1 | | 40.000+1.000=60.000 | | 67+x=282 | | -12+4x=6x-32 | | -4(2y+3)=(-18) | | 6/7y=9/14 | | -30=13x-80 | | 3/8k=3/4 | | x+2x+5+4x-7=0 | | 14=-2(x-3)+4 | | 8-7y=-34 | | -1/4x+15=-5 | | 3a+4b+2c=40 | | 9+(-4)x=13 | | -2(y-2)+3(4+3y)=-5 |